> 数学 >
(x+2)(x+4)(x+6)(x+8)=(x+2)^2+(x+4)^2+(x+6)^2+(x+8)^2
人气:412 ℃ 时间:2020-06-04 12:00:02
解答
(x+2)(x+4)(x+6)(x+8)=(x+2)^2+(x+4)^2+(x+6)^2+(x+8)^2
(x+2)(x+8)(x+4)(x+6)=x²+4x+4+x²+8x+16+x²+12x+36+x²+16x+64
(x²+10x+16)(x²+10x+24)=4x²+40x+120
(x²+10x)²+40(x²+10x)+384=4(x²+10x)+120
(x²+10x)²+36(x²+10x)+264=0
(x²+10x)²+36(x²+10x)+324=324-264
(x²+10x+18)²=60
x²+10x+18=±√60
x²+10x=±2√15-18
x²+10x+25=25±2√15-18
(x+5)²=7±2√15
有两个实数根,两个复数根.
x+5=±√(7±2√15)
x=±√(7±2√15)-5
推荐
猜你喜欢
© 2024 79432.Com All Rights Reserved.
电脑版|手机版